Jyapunhi Jatra of Panauti: Wonderful festival tourism product of Nepal - Lok Nath Dulal; Radha Adhikari; Surya Prasad Lakoju (Journal of Rural Tourism, 2025)
Purpose - This study examines Jyapunhi Jatra, a significant yet underrepresented intangible cultural heritage and festival tourism product of Panauti, Nepal. The research aims to explore its cultural relevance, celebration practices, and potential for tourism development.Methodology/Design/Approach - Using a qualitative approach with analytical and descriptive research design, the study draws on both primary data (interviews, observations) and secondary sources. Findings - Jyapunhi Jatra, held annually during Jestha’s full moon, embodies Panauti’s indigenous cultural identity through unique rites, processions, and customary practices. Despite its rich heritage value, the festival remains underutilized in the tourism sector.Originality/Value - This paper fills a gap in the documentation and promotion of Jyapunhi Jatra by highlighting its potential as a vibrant cultural tourism asset. It contributes to broader efforts to integrate intangible heritage into sustainable tourism strategies.